SOME NEW TYPE INTEGRAL INEQUALITIES FOR APPROXIMATELY HARMONIC h-CONVEX FUNCTIONS - Meftah, Badreddine; Kashuri, Artion (Matematichki Bilten, 2020)
In this paper, we present a new definition of preinvex functions depending on the given function which is called as approximately harmonic \(h\)-preinvex functions. We establish some inequalities of Hermite-Hadamard, Simpson and midpoint type for newly define class of functions. We show that this class contains several other new and known extensions of harmonic preinvexity. Special cases which can be deduced from the main results are also discussed in detail.